IMPROVING STUDENTS’ WRITING SKILL USING A MOBILE LEARNING APPLICATION - endar rachmawaty linuwih; Yohanes Kurniawan Winardi (BASIS (Bahasa dan Sastra Inggris), 2020)
Writing is claimed to be the most difficult skill for second language and foreign language learners. Thus, it needs an effective model of teaching to improve the students’ writing skill. This study aims to describe the use of a mobile learning application Busuu to improve students’ writing skill. This is a classroom action research (CAR) that was conducted into two cycles. Each cycle consisted two meetings and involved four steps namely planning, action, observation and reflection. The data were collected by using technique of observation, test, and interview. The subject of the research was fourteen students of Widya Kartika University. The result showed that there was an improvement in students’ writing skill. It can be seen from the result of writing test in each cycle which was improved. Mean score of the students’ writing in cycle 1 was 61.14 and the mean score of the students’ writing was 71.42 in cycle 2. In addition, the results of the interview showed that the students had a positive attitude toward the implementation of mobile learning application Busuu in the activities of learning writing.